The cult of zeus in ancient Lycaonia in the view of the inscriptions and its effects on social life - Kurt, Mehmet (Bartın Üniversitesi, 2024)
It is recognized that Zeus, with numerous different names, was idolized in many ancient regions of Anatolia. It is understood from the uncovered inscriptions that Zeus was worshiped in the Lycaonia Region with local epitets including Zeus'un akouseos, anaalpones, astlenos, bronton, dalbenos, megistos, stratios megistos, eukarpos, keraunios, phatnios, salarameus, soter, sozon, zemeiastes, zemroutenos. The inscriptions associated with Zeus Bronton, Zeus Megistos, Zeus Eukarphos, and Zeus Phatnios are more prevalent than the rest among these adjectives. These labels of Zeus provide tangible proof of his pivotal position in the societal and economic makeup of Lycaonia, an area primarily sustained by agriculture and animal breeding. Also, it can be noted that storm gods held a significant place of honor in Lycaonia, a fertile region that didn't receive substantial rain throughout its history, and this convention continued with Zeus. This research discusses the local Zeus cults in the Lycaonia region, based on iconographic and epigraphic sources, and their impact on the region's social life.

Zeus'un Anadolu'daki bir çok antik bölgede çok değişik epithetlerle tapınım gördüğü bilinmektedir. Ele geçirilmiş yazıtlardan Lykaonia Bölgesi'nde de Zeus'un akouseos, anaalpones, astlenos, bronton, dalbenos, megistos, stratios megistos, eukarpos, keraunios, phatnios, salarameus, soter, sozon, zemeiastes, zemroutenos gibi yerel epithetlerle tapınım gördüğü anlaşılmaktadır. Bu sıfatlar içerisinde özellikle Zeus Bronton, Zeus Megistos, Zeus Eukarphos ile Zeus Phatnios'ın geçtiği yazıtlar diğerlerine göre sayıca fazladır. Tanrının bu epithetleri temel geçim kaynağı tarım ve hayvancılık olan Lykaonia'nın sosyal ve ekonomik yapısında Zeus'un önemli bir yer tuttuğunun somut kanıtlarını oluşturmaktadır. Ayrıca en eski çağlardan itibaren verimli ancak yeterli yağmur almayan Lykaonia'da Fırtına tanrılarının en saygı gören tanrılar olduğu ve söz konusu geleneğin Zeus ile devam ettiği görülmektedir. Bu çalışmada ikonografik ve epigrafik kaynaklara göre Zeus'un Lykaonia Bölgesi'ndeki yerel kültleri ve bölgenin sosyal hayatına yansımaları ele alınmıştır.
Yazıtlar Işığında Antik Lykaonia'da Zeus Kültü ve Sosyal Hayata Etkileri
Keywords: Intangible Cultural Heritage; Somut Olmayan Kültürel Miras